2019
DOI: 10.14233/ajchem.2019.22151
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Molecularly Imprinted Polymer for the Removal/Extraction of Thymol from Spiked Blood Serum and River water

Abstract: Molecularly imprinted polymers (MIPs) were prepared by precipitation polymerization using thymol as a template molecule, acrylamide as a functional monomer and N,N-methylbisacrylamide as the crosslinker with a non-covalent approach. The polymers were characterized by scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), fourier-transform infra red spectroscopy(FT-IR) and Brunauer-Emmett-Teller (BET). The SEM results depicted that the shape of polymer particles is spherical with unifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, it is not possible to establish a predicted trend for MIPs adsorption capacity toward target molecules with increasing or decreasing pH, as it depends on the most favorable chemical environment in which they are involved. Indeed, Bakhtiar et al [116] found a decrease in MIPs adsorption capacity of 20% toward 2-phenilphenol when the pH was different from 7. Again, Dai and Cortalezzi [117] reported an increase in the adsorption capacity of a MIPs sensor toward 2,4 di-nitrotoluene as the pH value increased.…”
Section: Enhanced Removal Of Cecs Via Mipsmentioning
confidence: 99%
“…However, it is not possible to establish a predicted trend for MIPs adsorption capacity toward target molecules with increasing or decreasing pH, as it depends on the most favorable chemical environment in which they are involved. Indeed, Bakhtiar et al [116] found a decrease in MIPs adsorption capacity of 20% toward 2-phenilphenol when the pH was different from 7. Again, Dai and Cortalezzi [117] reported an increase in the adsorption capacity of a MIPs sensor toward 2,4 di-nitrotoluene as the pH value increased.…”
Section: Enhanced Removal Of Cecs Via Mipsmentioning
confidence: 99%
“…According to the approach used to prepare these MIPs, we can find up to three families [ 29 ]. First, the non-covalent imprinting approach: this procedure is based on relatively weak interactions such as electrostatic and hydrophobic interactions, hydrogen bonding or π-π bonding established between the template and structural polymer [ 30 , 31 , 32 , 33 ]. In second place, the covalent approach is based on covalent bond formation between the template molecule and the functional monomer before polymerization; once the polymer has been synthesized, the template molecule is extracted from the 3D-network disrupting the covalent bonds.…”
Section: Introductionmentioning
confidence: 99%